JPRS Report Science & Technology USSR: Earth Sciences. - JOINT PUBLICATIONS RESEARCH SERVICE ARLINGTON VA (1987)
Partial Contents: Meteorology, CLimate, Oceanography, Radar Guides, Rescue, Plankton, Digital Temperature, Propagation, Terrestrial Geophysics, Physics of Atmosphere, Arctic and Antarctic Research.